2021
DOI: 10.3390/math9212773
|View full text |Cite
|
Sign up to set email alerts
|

Currency Hedging Strategies Using Histogram-Valued Data: Bivariate Markov Switching GARCH Models

Abstract: Previous studies aimed at determining hedging strategies commonly used daily closing spot and futures prices for the analysis and strategy building. However, the daily closing price might not be the appropriate for price in some or all trading days. This is because the intraday data at various minute intervals, in our view, are likely to better reflect the information about the concrete behavior of the market returns and reactions of the market participants. Therefore, in this study, we propose using high-freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Salisu et al [14] mentioned that financial assets had reacted differently to inflation due to their vulnerability to structural changes in the economy. Maneejuk et al [62] also revealed that the ability of an asset to hedge inflation may be subject to the state of economies, such as stable and turbulent economic regimes. An asset could easily hedge against inflation during the stable regimes; however, it was evident that assets were unable to hedge against inflation and lost their valuation during the turbulent [3,16].…”
Section: Methodology Issuesmentioning
confidence: 99%
“…Salisu et al [14] mentioned that financial assets had reacted differently to inflation due to their vulnerability to structural changes in the economy. Maneejuk et al [62] also revealed that the ability of an asset to hedge inflation may be subject to the state of economies, such as stable and turbulent economic regimes. An asset could easily hedge against inflation during the stable regimes; however, it was evident that assets were unable to hedge against inflation and lost their valuation during the turbulent [3,16].…”
Section: Methodology Issuesmentioning
confidence: 99%
“…Although the COVID-19 pandemic is a unique opportunity to test Bitcoin's inflation-hedging properties, it is crucial to acknowledge potential influences from this atypical event. 8 As highlighted by Maneejuk et al (2021), an asset's ability to hedge against inflation may be subject to the state of the economy, encompassing both stable and turbulent economic regimes. Taking into account this possibility, the model was re-estimated using data up to December 2019.…”
Section: Changing Sample Period: Before Covid-19mentioning
confidence: 99%